Вычислительные машины, системы, комплексы: справочник / А. П. Заморин, А. А. Мячев, Ю. П. Селиванов - Заморин Анатолий Петрович (Энергоатомиздат, 1985)
Экземпляры: КХ (20170420) / Инвентарный номер: 863773 / Сис.шифр: 621.38 / Авт.знак: З-26 / ГРНТИ: 47 / ББК: 32